Pendidikan Kesehatan bagi Ibu Hamil dengan Tema “Pentingnya Anc Rutin dan Mengenal Tanda Bahaya dalam Kehamilan” - Tilawaty Aprina; Yenny Puspitasari; Nurhasanah Nurhasanah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Maternal health is crucial to ensure the safety and well-being of both the mother and fetus, and therefore requires continuous monitoring through communication, education, and antenatal care (ANC). However, low adherence to ANC visits remains a challenge, as it delays the early detection of risks and contributes to persistently high maternal and infant mortality rates in Indonesia. This community service program was conducted at the Sui Raya Dalam Public Health Center, Kubu Raya Regency, with the aim of improving pregnant women’s knowledge of ANC and pregnancy danger signs. A total of 41 respondents participated in the intervention, which utilized video-based education, online forms distributed via WhatsApp, and a structured pre-test and post-test evaluation to measure knowledge improvement. The findings revealed a strong positive and statistically significant correlation (r = 0.580, p = 0.001) between pre-test and post-test scores. This result demonstrates that health education is effective in enhancing pregnant women’s knowledge, particularly regarding the importance of routine ANC visits and recognizing pregnancy danger signs. Moreover, the integration of digital platforms such as videos and mobile applications proved beneficial in delivering accessible and engaging health information. In conclusion, health education is a practical and impactful strategy to strengthen maternal knowledge and awareness. Collaborative approaches that combine conventional health services with digital technologies can help overcome resource limitations in primary health care and contribute to reducing maternal and infant mortality rates.